Empirical Evidence on the Mediating Role of Attitude Between Environmental Concern and Perceived Usefulness toward Electric Motorcycles Adoption Intentions Among Female Gen Z - Narayani, Ni Komang Prema; Hanafiah, Ali (Jurnal Ilmiah Manajemen dan Bisnis, 2025)
The global reliance on fossil fuels has intensified the energy crisis and worsened urban air pollution, creating an urgent need for sustainable transportation solutions. Electric motorcycles offer a promising alternative, especially in Indonesia where motorcycle use is widespread. This study investigates the influence of environmental concern and perceived usefulness on the intention of female Gen Z consumers to adopt SELIS electric motorcycles, with attitude toward electric motorcycles as a mediating variable. Data were collected through a structured online questionnaire using purposive sampling and analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM) in SmartPLS. The findings reveal that both environmental concern and perceived usefulness significantly enhance intention to use, while also shaping favorable attitudes toward electric motorcycles. Attitude itself exerts a strong positive influence on intention and mediates the relationships between the independent variables and intention. These results highlight that adoption decisions are driven not only by ecological awareness but also by functional value, with attitude reinforcing this effect. The study concludes that strategies integrating sustainability messages with practical benefits are essential to encourage wider adoption of electric motorcycles among female Gen Z consumers.